PENGARUH LIKUIDITAS, KECUKUPAN MODAL DAN EFISIENSI OPERASIONAL TERHADAP PROFITABILITAS PADA PERBANKAN YANG TERDAFTAR DI BEI - Listiyawan, Heri; Probowati, Anna; Nugrahani, Dewi Shanti; Sucipto, Adi (Jurnal Akuntansi dan Pajak, 2024)
This study aims to analyze the effect of liquidity, capital adequacy and operational efficiency on profitability in banking companies listed on the IDX. This study uses a quantitative approach using data from the company's annual financial statements. Research respondents are banking companies listed on the Indonesia Stock Exchange. The sample is the annual report of banking companies listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling with a research sample of 29 respondents. Methods of data analysis using multiple linear regression test. The results of the calculation of the Coefficient of Determination (R2) show that the contribution of liquidity, capital adequacy and operational efficiency to ROA in banking companies listed on the IDX is 18%, while the remaining 82% is influenced by other factors not included in the analysis of this study. Based on the statistical results of the t test, it was concluded that liquidity had no significant effect on ROA, capital adequacy had no significant effect on ROA, the operational efficiency variable had no significant effect on ROA. Based on the statistical results of the F test, it is concluded that liquidity, capital adequacy and operational efficiency simultaneously (simultaneously) have no significant effect on profitability. Keywords: liquidity, capital adequacy, operational efficiency.